Wake-up call for recovery: a paradigm shift to address the deep crisis in Israel’s public mental health services in the shadow of October 7, 2023 - Amir Krivoy; Gadi Rosenthal (Israel Journal of Health Policy Research)
Abstract Background The events of October 7, 2023, and the subsequent war have starkly exposed the shortcoming of Israel’s public mental health system. This system, already strained by years of underfunding and the COVID-19 pandemic, was unprepared for the surge in mental health needs resulting from these traumatic events. This paper outlines the systemic failures and proposes a comprehensive overhaul reform towards an integrative community-based, recovery-oriented mental health service. Main body Israel’s mental health crisis is exacerbated by four converging vectors: a global diagnostic crisis in psychiatry, insufficient biological treatments, chronic underfunding, and a fragmented service model. Diagnostic practices, centered on outdated classifications, fail to address the complexity of severe mental illnesses, resulting in imprecise diagnoses and insufficient treatments. Despite the advent of psychopharmacology, significant advancements in drug efficacy are lacking, with recovery rates stagnating or declining. Financially, mental health in Israel receives only 5.2% of the health budget, far below the 10–16% seen in high-GDP Western countries. The community mental health services reform in 2015 lack effective oversight and incentives, leading to long wait times and inadequate care. Additionally, the fragmentation among funding entities—HMOs, Ministry of Health, and Ministry of Welfare—hampers coordinated care and comprehensive service delivery. Conclusion The proposed solution involves shifting from a hospital-biomedical -based to an integrated community-based model, emphasizing recovery over symptom management, based on regional mental health centres as hubs of services. This requires significant investment in community mental health teams, crisis intervention, home treatment, and integrated services. Early intervention, technology utilization, economic incentives for community-based care, and patient and family involvement are crucial components. This transformation aims to create a holistic, efficient, and patient-centered mental health system, better equipped to handle future challenges and reduce the societal and economic burdens of mental illness in Israel.